THE SURFACE CHARACTER OF Staphylococcus aureus ISOLATED FROM SUBCLINICAL MASTITIS OF DAIRY COW SUPPORTING ADHERENCE TO UDDER EPITHELIAL CELL - Wahyuni, A.E.T.H.; Winarso, D.; Valenti, V.; Franky, F. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
Staphylococcus aureus (S. aureus) is one among pathogen bacteria that caused mastitis in dairycow in Indonesia. Its ability to initiate infection depends on the surface character of the bacteria. Thesurface character of S. aureus is determined by the corelation of red blood cell hemagglutination activity,hydrophobicity, production of protein A, and bacterial adherence to the mammary epithelial cells of thehost. This research was designed to characterize the surface of S.aureus, which correlates to bacterialadherence. Four isolates of S. aureus were taken from subclinical mastitis milk of dairy farm in Malang,East Java. The surface character of S.aureus was determined by performing the red blood cellhemagglutination test using the dairy cow erythrocyte suspension with concentration of 0.5%, 1%, and2%. The hydrophobicity expression was determined by Salt Aggregation Test (SAT) method using theAmmonium Sulfate suspension with concentration of 1.2 M, 1.6 M, 2.0 M, 2.4M, and 3.2 M. Serum softagar (SSA) test was used to indicate the production of protein A; Ability of adhesion was done byadhering the S.aureus, which were already labelled by Fluorescent Ichtiocyanate (FITC) to themammary epithelial cell of post-calving mice. Result of this this research showed that the surfacecharacters of S.aureus, which correlates to the adherence, comprise of erythrocytes hemagglutinationability, hydrophobicity, and protein A production. Isolates of S.aureus, which is hydrophobic, possesshaemagglutinine, and protein A were able to adhere to mammary epithelial cell with higher quantity